Air-Sea Trace Gas Fluxes: Direct and Indirect Measurements - Fairall, Christopher W.; Yang, Mingxi; Brumer, Sophia E.; Blomquist, Byron W.; Edson, James B.; Zappa, Christopher J.; Bariteau, Ludovic; Pezoa, Sergio; Bell, Thomas G.; Saltzman, Eric S. (Frontiers in Marine Science, 2022)
The past decade has seen significant technological advance in the observation of trace gas fluxes over the open ocean, most notably CO2, but also an impressive list of other gases. Here we will emphasize flux observations from the air-side of the interface including both turbulent covariance (direct) and surface-layer similarity-based (indirect) bulk transfer velocity methods. Most applications of direct covariance observations have been from ships but recently work has intensified on buoy-based implementation. The principal use of direct methods is to quantify empirical coefficients in bulk estimates of the gas transfer velocity. Advances in direct measurements and some recent field programs that capture a considerable range of conditions with wind speeds exceeding 20 ms-1 are discussed. We use coincident direct flux measurements of CO2 and dimethylsulfide (DMS) to infer the scaling of interfacial viscous and bubble-mediated (whitecap driven) gas transfer mechanisms. This analysis suggests modest chemical enhancement of CO2 flux at low wind speed. We include some updates to the theoretical structure of bulk parameterizations (including chemical enhancement) as framed in the COAREG gas transfer algorithm.